How can I prove #b^(x+y)=b^xb^y# by using #b^x=e^(xln(b))# ?

1 Answer
Write your answer here...
Start with a one sentence answer
Then teach the underlying concepts
Don't copy without citing sources
preview
?

Answer

Write a one sentence answer...

Answer:

Explanation

Explain in detail...

Explanation:

I want someone to double check my answer

Describe your changes (optional) 200

2
Feb 9, 2018

Answer:

# \ #

# "Please see proof below." #

Explanation:

# \ #

# "We compute as follows, using the rule you provided," #
# "to be taken as a given:" #

# b^{x+y} \ = \ e^{ (x+y) ln(b) } \ = \ e^{ [ x ln(b)+ y ln(b)] } \ = \ e^{ x ln(b) } \cdot e^{ y ln(b) } #

# \qquad \qquad \ = \ b^{x} \cdot b^{y}. \qquad \qquad \qquad square #

Was this helpful? Let the contributor know!
1500